2018
DOI: 10.1007/s00381-017-3699-0
|View full text |Cite
|
Sign up to set email alerts
|

The oscillatory flow of the cerebrospinal fluid in the Sylvian aqueduct and the prepontine cistern measured with phase contrast MRI in children with hydrocephalus—a preliminary report

Abstract: IntroductionRecognizing patients with ventriculomegaly who are at risk of developing acute hydrocephalus presents a challenge for the clinician. The association between disturbed cerebrospinal fluid flow (CSF) and impaired brain compliance may play a role in the pathogenesis of hydrocephalus. Phase contrast MRI is a noninvasive technique which can be used to assess CSF parameters. The aim of the work is to evaluate the effectiveness of phase contrast MRI in recognizing patients at risk of acute hydrocephalus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The goal of the present study was to characterize CSF flow dynamics and geometry in people with ALS compared to healthy controls. A few groups have made strides towards characterizing CSF dynamics in conditions such as Chiari malformation [15][16][17][18][19][20][21], Syringomyelia [20][21][22], and hydrocephalus [23], as well as investigation of CSF flow dynamics in people with ALS [24]. We expand on this characterization by providing a more complete analysis of the hydrodynamic environment.…”
mentioning
confidence: 99%
“…The goal of the present study was to characterize CSF flow dynamics and geometry in people with ALS compared to healthy controls. A few groups have made strides towards characterizing CSF dynamics in conditions such as Chiari malformation [15][16][17][18][19][20][21], Syringomyelia [20][21][22], and hydrocephalus [23], as well as investigation of CSF flow dynamics in people with ALS [24]. We expand on this characterization by providing a more complete analysis of the hydrodynamic environment.…”
mentioning
confidence: 99%
“…[ 14 ] In pediatric cases with an enlarged cerebral ventricle, poor pulsation in the prepontine cistern can be detected using cine MRI, unlike in asymptomatic cases. [ 8 ] Moreover, a study by Anik et al . reported that good pulsation in the prepontine cistern can be observed after ETV in successful cases of BPC in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar investigations using phase‐contrast MRI have been repeated by other groups (Miyazaki et al, 2019). To explain the underlying pathophysiology, CSF flow studies have been undertaken (Nowosławska et al., 2018). These studies are based on cardiac‐gated MRI phase contrast and could demonstrate that the strength of the flow void signal (Figure 7) through the aqueduct predicts the success rate by shunt therapy.…”
Section: Disorders Of Csf and The Astrocytic Networkmentioning
confidence: 99%